Vibrational Hamiltonian of Carbonyl Sulphide and Hydrogen Cyanide - K. Lavanya; A. Ganapathi Rao; J. Vijayasekhar (East European Journal of Physics, 2024)
This study thoroughly investigates the vibrational frequencies of carbonyl sulphide (12C16O32S) and hydrogen cyanide (HCN) up to the fifth harmonic level. It offers comprehensive insights into vibrational modes by using the Hamiltonian operator formalism and concentrating on invariant operators and algebraic parameters with a one-dimensional Lie algebraic method. The findings are significant for atmospheric chemistry, spectroscopy, and quantum chemistry, contributing to a deeper understanding of molecular dynamics. This research sets the groundwork for future studies in comparable compounds and applications.